"Green is Where it's At!" Cultivating Environmental Concern at an African American Church. (24th February 2015) - Baugh, Amanda
Abstract : Since the 1990s much 'religion and ecology' scholarship has sought to identify theological, ethical, and scriptural resources that suggest all religions teach their followers to protect the earth. Case studies have focused primarily on success stories that demonstrate how religions can contribute to a more sustainable future, but religion and ecology scholarship has paid inadequate attention to cultural complexities involved with cultivating environmental concern in religious communities. This article aims to address some of those neglected factors. A bible study on food, faith, and the environment held at an African American church in Chicago offers a glimpse into a window for exploring how assumptions about ethnicity and class influence the presumed 'greening' of American religion. I argue that efforts to 'green' American religion have relied not only on religious teachings, but also on latent assumptions about ethnicity and class.